A GENERAL ASSESSMENT OF BADR AL-DIN AL-AYNI’S PERSPECTIVES ON AMIR TIMUR (Scientific journal of the Fergana State University, 2026)
Badr al-Din al-Ayni (1361–1451) was a prominent jurist and historian who worked in Egypt. In his extensive historical works, he paid special attention to the political, cultural, and social developments in the region of Transoxiana. Al-Ayni provides a thorough analysis of the Timurid era. His work “Iqd al-Juman fi Tarikh Ahl al-Zaman” (“Pearls on the History of Contemporaries”) offers detailed accounts of Amir Temur and his successors’ political activities, military campaigns, governance, and contributions to the advancement of science and culture. Al-Ayni portrays Temur as a skilled commander and a just ruler. He speaks positively about the prosperity of Samarkand, its madrasahs, and libraries. The work also contains valuable information on the Timurid dynasty’s diplomatic relations with Egypt and other countries. Al-Ayni compares the political stability of Transoxiana with other regions of the Islamic world and acknowledges the region’s advanced development in science, culture, and economy. His approach combines that of an impartial historian and a religious scholar. Justice in governance, preservation of religious values, and support for knowledge were key criteria for him. Therefore, he describes Transoxiana as one of the most influential scientific centers in the Muslim world of that time.